Enhancement of Financial Inclusion through Islamic Fintech with Value-Based intermediation, a proposed second phase for the Islamic Banking industry - YOUSUFZAI, SHAH FAHAD; HAYAT, ARSHAD; ABBAS, MUHAMMAD HASSAN (International Journal of Islamic Economics and Governance, 2023)
Nowadays, almost every bank is trying to come up with cutting-edge technology products and services. It is the trend of the market and need of the hour too. Through these products and services, Islamic Banks can retain their existing customers and also can add new customers, which will enable them to achieve their financial inclusion plan. Ultimately Islamic banks will achieve greater revenue by adding innovative digital products and services. Covid19 compelled the financial sector to develop innovative technology-based products in order to avoid in-person interactions. Financial institutions can achieve their goal by protecting both their employees and their customers by adhering to the standard operating procedures issued by the relevant Islamic banks. There are people in a society who have relationships with financial institutions, but there are also people who have no relationships with any financial institutions. Developing emerging economies are frequently eager to bring their unbanked citizens into the banking and financial sectors, believing that it will help them improve their social and economic lives. Financial inclusion is also used to alleviate poverty. The study’s focus is on financial inclusion through Fintech and how to use Technology in Islamic Finance to improve financial inclusion through value-added propositions. This is a modern trend in the financial sector in which every financial institution wants to provide cutting-edge technology services to customers while also increasing revenue and fee-based income.